2020
DOI: 10.1002/slct.201904730
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient Solar‐Catalytic Degradation of Reactive Black 5 Dye Using Mesoporous Plasmonic Ag/g‐C3N4 Nanocomposites

Abstract: An azo dye, Reactive Black 5 (RB5), was degraded by three photocatalysts of g‐C3N4, Ag(2 %)/g‐C3N4, and Ag(5 %)/g‐C3N4 with the specific surface areas of 34.41, 28.70, and 35.58 m2 g−1 and the band gaps of 2.52, 1.56, and 1.71 eV under sunlight illumination, respectively. The results showed 40 mg/L of g‐C3N4 could degrade completely 10 ppm RB5 at pH 3.4 within 10 min under sunlight irradiation with the first‐order rate constant of 0.312 min−1. Under the same conditions, the complete degradation time of RB5 red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…There are several reports available on the synthesis of plasmonic NP decorated GCN through thermal condensation of available precursors followed by photodeposition of plasmonic NPs. 58–61 In one such report Wei et al 62 synthesized Ag decorated GCN nanosheets via thermal condensation of urea. A weighed amount of urea was taken in an alumina crucible and heated at 550 °C with a heating rate of 2.5 °C min −1 in a muffle furnace for 4 h. After 4 h, the crucible was allowed to cool and the obtained GCN powder was crushed to a fine powder for further use.…”
Section: Synthesis Strategies For Plasmon Mediated Gcnmentioning
confidence: 99%
“…There are several reports available on the synthesis of plasmonic NP decorated GCN through thermal condensation of available precursors followed by photodeposition of plasmonic NPs. 58–61 In one such report Wei et al 62 synthesized Ag decorated GCN nanosheets via thermal condensation of urea. A weighed amount of urea was taken in an alumina crucible and heated at 550 °C with a heating rate of 2.5 °C min −1 in a muffle furnace for 4 h. After 4 h, the crucible was allowed to cool and the obtained GCN powder was crushed to a fine powder for further use.…”
Section: Synthesis Strategies For Plasmon Mediated Gcnmentioning
confidence: 99%
“…However, these materials suffered from some insufficiencies: (1) LDHs and clays exhibit slow sorption kinetics and limited selectivity; (2) ACs and carbonaceous materials possess disadvantages of small pore volumes or pore sizes; (3) GO and CNTs are complicated to synthesize and produce; (4) the poor regeneration and reusability of organic resins; and (5) relatively low chemical and thermal stability of LMS. 147 Novel nanomaterials, such as polymer adsorbents, 148 2D MXenes, 149 , 150 , 151 , 152 , 153 nanoscale zero-valent iron (NZVI), 154 , 155 , 156 , 157 , 158 , 159 g-C 3 N 4 , 120 , 160 , 161 , 162 , 163 , 164 MOFs, 165 , 166 , 167 , 168 and COFs, 169 , 170 , 171 are constantly applied to improve their applications in environmental pollution cleanup owing to their superior performance. MOFs and COFs represent porous crystalline materials for network topology.…”
Section: Introductionmentioning
confidence: 99%
“…They found that superoxide radical is essential for the photocatalytic decomposition of the RB5 along with * OH radicals supplementary effect for this process. [31] However, the photocatalytic degradation efficiency of crosslinked chitosan/Au nanocomposite was investigated, which resulted in rapid and efficient photodegradation of RB5, as reported by Midya et al. [32] Although many studies have been reported in the related literature concerning the photocatalytic activity, mainly of TiO 2 and ZnO, the effectiveness of these catalysts for RB5 degradation has not been thoroughly and comparatively investigated yet.…”
Section: Introductionmentioning
confidence: 99%
“…Although many studies have been reported in the related literature concerning the photocatalytic activity, mainly of TiO 2 and ZnO, the effectiveness of these catalysts for RB5 degradation has not been thoroughly and comparatively investigated yet. However, RB5 is in the group of azo dyes, one of the most used dyes in the textile industry [31] . Therefore, in this study, the photocatalytic removal efficiency of TiO 2 and ZnO has been comprehensively investigated for RB5 photodegradation.…”
Section: Introductionmentioning
confidence: 99%